Buckling of pre-twisted threads embedded in a soft matrix - Mohammad Redowan (Nanyang Technological University, 2024)
Wearable electronics or technology has been on the rise for some time and the importance of it has been all-time high. Continuing the previous research, electronic components, being brittle and rigid, will face curvilinear forces when exposed to curved surfaces. Controlling the buckling of the threads in the soft matrix will give electronic materials the flexibility they require to conform to their specific shape. A compressive force will be exerted, and the data obtained from that will give us a good indication of the way the wire behaves. This will also help determine the right type of silicone that can be used for this experiment. Silicone was chosen for this experiment as it is transparent for us to visibly track the buckling of the wire within the mold itself. Subsequently, polyurethane was also chosen for the same properties of being transparent and soft. Competent results were unfortunately not obtained for the silicone material. However, for the polyurethane mixture, it was successful and possible. The discussions here in the report will dive into the entire process and what can be done next in the future.